Communication and collaboration: an exploration of clinical governance Interventions in the Western Cape Department of Health over the past twenty years - Singh, Yesheen (Department of Public Health and Family Medicine, 2021)
Background: The tension between the increasing cost of healthcare provision and the need to provide a quality level of care to a rising number of people is a global phenomenon. A focus on one over the other could result in a rise in adverse patient outcomes, or a health system too costly to be sustainable. Clinical governance is an approach policymakers can use to walk the middle line of creating a healthcare service that meets quality of care standards in a cost-effective manner, as has been done in Australia, Burundi, Egypt, Spain, UK and Yemen (Goyet et al, 2019; Abd El Fatah et al, 2019, Mannion et al, 2015; Aguilar Martin et al, 2019). This study examines the practice of clinical governance in one LMIC setting that has been able to successfully do this balancing walk for 20 years. Understanding how this was done in the Western Cape province of South Africa helps inform how clinical governance can be used to continue adding value as the health system moves towards universal healthcare. In addition, this South African experience adds to the still small pool of relevant experience from low- and middle-income countries reported in the international literature. Methods: A mixed methods qualitative design was used for data collection and involved three phases: (1) a document review of all policies in the province to identify clinical governance structures; (2) observation of these structures in action, comparing lived to written experience of clinical governance; and (3) interviews with key stakeholders in the province to get their perspectives on past, present and future forms of clinical governance. The Donabedian model was used to frame analysis into three dimensions of care, viz. structure, process and outcome. Results: Beyond a comprehensive policy framework, collaborative structures and consultative leadership styles facilitated strengthened clinical governance in the Western Cape. For example, although corporate-governance-inspired structures, such as clinical audits and M&E events, may become punitive and corrosive, the potential negative impact on clinical governance outcomes and organisational culture was tempered by healthy communication and supportive relationships between colleagues. Family physicians have become the champions of clinical governance in a decentralized health system and when supported in this by policy and management, the quality of care in health systems thrive. Conclusions Clinical governance is an effective strategy or tool LMICs can use to ensure quality of care is maintained or improved upon, even in resource-challenged settings. But while some structures, processes and outcomes may be borrowed from other LMIC or HIC settings, these need to be contextualized to local conditions. Appropriate clinical governance champions need to be identified and given the appropriate mandate. Human relationships are key to the successful implementation of interventions of this nature and space needs to be created in policy for this to be cultivated.